Risk factors associated with anaemia among pregnant women in the Adaklu District, Ghana - Eric Tettegah; Thomas Hormenu; Nancy Innocentia Ebu-Enyan (Frontiers Media S.A., 2024)
BackgroundAnaemia during pregnancy is a major public health concern in both advanced and less-developed countries including Ghana. The prevalence of anaemia in Ghana has a serious repercussion on the country's social and economic development. This prevalence has been linked to various factors, including educational level and occupational status.MethodsA prospective study was conducted to investigate the factors influencing anaemia among 150 pregnant women, aged 15-49 years, who attended antenatal clinics in the Adaklu District of the Volta region of Ghana. Haemoglobin levels were assessed in the first, second, and third trimesters, and a questionnaire was also used to collect data on demographic information and barriers to maintaining haemoglobin levels. The data were analysed using frequencies, percentages, and binary logistic regression.ResultsThe prevalence of pregnancy anaemia in the district was 78.5%. The study found that 92% and 8% of pregnant women had excellent and good knowledge on anaemia in pregnancy, respectively. The study also identified several barriers to maintaining an appropriate haemoglobin level during pregnancy, such as long distances to healthcare facilities, non-intake of antimalarial drugs, and lack of nutritious meals. Finally, the study found that low education level, number of pregnancies, and number of children a woman had were significant determinants of anaemia during pregnancy in the district.ConclusionThe findings of the study suggest that targeted interventions are needed to reduce the burden of anaemia during pregnancy in the district. These interventions should address the social and environmental determinants of anaemia during pregnancy, such as improving access to healthcare facilities and promoting healthy eating habits. In addition, interventions that address social determinants of health, such as education and occupation, may be effective in reducing the burden of anaemia during pregnancy in the district.